The Relationship Between Substance Abuse Proclivity and Spiritual Well-Being Levels of University Students in Turkiye - Dogan, Ufuk; Avci, Sezer (Springer, 2025)
Focusing on young adults constituting the most vulnerable and risky group regarding substance abuse, the present study was carried out in order to examine the relationship between the spiritual well-being levels of university students and their substance abuse proclivity. Having a descriptive and cross sectional design, this study was completed with 250 students studying at a Vocational High School of a university in T & uuml;rkiye during the academic year 2021-2022. The data collection process was carried out by using the Personal Information Form, the Spiritual Well-Being Scale (SWBS), and the Substance Use Tendency Scale (SAPS). In this study, students' level of spiritual well-being was found to be high. This was determined according to the 'Transcendence' sub-dimension of the SWBS scale (67.13 +/- 7.09). It was found that 39.2% of the students had a substance abuse proclivity. It was also determined that all university students had total scores on the SAPS below the cutoff point (14.99). However, a considerable portion of the students (39.2%) scored 16 or higher on the scale, which indicates a substance abuse proclivity. The results obtained in this study revealed that the high level of spirituality plays an effective role in moderately reducing the substance abuse proclivity (r = - 0.367; p < 0.05). Programs aiming to improve spirituality, emphasize the importance of family relationships, social order, nature walks, and strengthen existing religious beliefs should be provided to university and high school students.
Keywords: Spirituality; Well-being; Substance abuse proclivity; University students